APOS - antibiotic prophylaxis for preventing infectious complications in orthognathic surgery: study protocol for a phase III, multicentre, randomised, controlled, double blinded, clinical trial with two parallel study arms - Ristow, Oliver; Hofele, Christof; Münch, Philipp; Danner, Sylvia; Dietzel, Anja; Krisam, Johannes; Klose, Christina; Pilz, Maximilian; Hoffmann, Jürgen; Freudlsperger, Christian (Trials, 2021)
It is a constant debate among surgeons whether the use of prolonged postoperative antibiotics may reduce surgical site infection rates. As specific treatment guidelines are still lacking, many surgeons continue to use broad-spectrum antibiotics, causing not only increased costs but also contributing to the potential for antibiotic resistance. Hence, there is an urgent need for an appropriately designed prospective clinical trial, to investigate whether a prophylactic use of antibiotics after surgery actually decreases surgical site infections to a clinically relevant degree.